Aspectos epidemiológicos da raiva animal e avaliação da diversidade de morcegos e de seus ectoparasitas na microrregião Quirinópolis, Goiás, Brasil - Teixeira, Laura Helena Marcon (2013)
Pneumonia is of the main causes of death of children under 5 years of age. Several health organizations worldwide, public and private, are engaged in investigating the disease and evaluate the effectiveness of mechanisms to prevent and combat existing. Infections causing pneumonia can be avoided. However, especially in poor countries, the resources to promote prevention are scarce. Thus the combat actions need to be very efficient and effective. To ensure the effectiveness of these actions, such as vaccines, are necessary statistical information like age range, region, period, social status and history obtained through field research. This paper proposes and implements a software architecture for the construction, use and maintenance of research of childhood pneumonias. The techniques, technologies, tools and services used in defining the architecture were chosen with a focus on low cost. This way is much more feasible to use software for automated search systems by healthcare entities that have few financial resources.